The Influence of an Attachment-Related Stimulus on Oxytocin Reactivity in Poly-Drug Users Undergoing Maintenance Therapy Compared to Healthy Controls - Fuchshuber, Jürgen; Tatzer, Jasmin; Hiebler-Ragger, Michaela; Trinkl, Florian; Kimmerle, Andreas; Rinner, Anita; Buchheim, Anna; Schrom, Silke; Rinner, Beate; Leber, Klaus; Pieber, Thomas; Weiss, Elisabeth; et al. (Frontiers in Psychiatry, 2020)
Background: Substance use disorders (SUD) have been described as a dysfunctional way to compensate for deficiencies in that person’s underlying attachment system. Furthermore, the neuropeptide Oxytocin (OT), which is a critical component of the neurobiology of the attachment system, has been shown to effectively reduce addictive behavior and therefore has been discussed as a potential medication in SUD treatment. This study investigates variation in peripheral OT plasma levels as a function of exposure to an attachment-related stimulus in SUD patients compared to healthy controls (HC). Methods: A total sample of 48 men, 24 inpatients in maintenance treatment who were diagnosed with poly-drug use disorder (PUD) and 24 HC, was investigated. A 15 minute exposure to the Adult Attachment Projective Picture System (AAP) was used as an attachment-related stimulus and coded for attachment status. Blood samples before and after the AAP-assessment were taken and assayed for OT levels. Variation in baselines level of OT were examined in relation to the Alcohol, Smoking and Substance Involvement Screening Test (ASSIST), the Adult Attachment-Scale (AAS), and the Brief Symptom Inventory (BSI). Results: Following the AAP stimulus controls showed no significant difference in OT levels elevation from baseline compared to the PUD group’s OT levels. Furthermore, in the PUD group only OT-baseline-levels may be negatively associated with the AAS subscale “Comfort with Closeness” and “Anxiety” and lifetime substance use Discussion: Our results suggest that peripheral OT levels in poly-drug users undergoing maintenance treatment are not significantly different in responsiveness to an attachment related stimulus compared to healthy controls. With regard to non-significant tendencies observed in this study which hint towards decreased OT-reactivity in the PUD group, further research is needed to explore this hypothesis with increased statistical power.